Preoperative Thyroid Peroxidase Antibody Predicts Recurrence in Papillary Thyroid Carcinoma: A Consecutive Study With 5,770 Cases - Wang, Weibin; Wen, Liping; Chen, Shitu; Su, Xingyun; Mao, Zhuochao; Ding, Yongfeng; Chen, Zhendong; Chen, Yiran; Ruan, Jiaying; Yang, Jun; Zhou, Jie; Teng, Xiaodong; et al. (Frontiers in Oncology, 2022)
Background: Thyroid autoimmunity is common in papillary thyroid carcinoma (PTC) and was believed to confer a better prognosis whereas controversy still remains. This study aimed to investigate the prognostic value of chronic lymphocytic thyroiditis (CLT) and preoperative thyroid peroxidase antibody (TPOAb) in PTC patients. Methods: A retrospective analysis was performed on 5770 PTC patients who underwent surgical treatment with pathologically confirmed PTC in out institution between 2012 to 2016. Patients were divided into groups with respect to the coexistence of CLT or preoperative TPOAb levels. Clinicopathological characteristics and disease-free survival (DFS) rates were compared between groups. Results: Coexistence of CLT was likely to have bilateral, multifocal tumors. Particularly, PTC patients with TPOAb ++ (> 1000 IU/L) had larger tumor size (p = 0.007), higher rates of bilaterality and multifocality than those with TPOAb − (TPOAb < 100 IU/L). While for lymph node metastasis and extrathyroidal extension, there is no statistic difference. Tumor recurrence was found in 15 of 425 (3.5%), 9 of 436 (2.1%) and 56 of 3519 (1.6%) patients with TPOAb ++, TPOAb + and TPOAb − respectively (p = 0.017). On univariate analysis, TPOAb ++ was correlated with tumor recurrence with a hazard of 2.20 [95% confidence interval (CI), 1.25-3.89], which remained as an independent risk factor at 1.98 (95% CI, 1.10-3.55) on multivariate analysis. PTC patients with TPOAb ++ had the lowest DFS rates (96.5% vs. 97.9% vs. 98.4%, p = 0.020). Conclusion: CLT is not a protective factor in PTC patients. Instead, we provide initial evidence that the preoperative TPOAb predicts recurrence in papillary thyroid carcinoma.